Evaluation of micropollutant toxicity in Ergene river during a dry month - Eken Türkoğlu, Özgücan. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2019., 2019)
In this study, micropollutant analyses were carried out on water samples taken from Ergene River in August 2017. Additionally, acute toxicity values of each sample were determined by using Microtox test and relationship between micropollutants and toxicity was investigated. About 222 micropollutants analyzed in samples, 131 of which were detected at least once. Among them were priority pollutants, antibiotics, brominated flame retardants, nonylphenols, disinfectants, pesticides, plasticizers, fragrances and cyanotoxins. Benzyldimethyldodecylammonium (BAC-12), benzyldimethyltetradecylammonium (BAC-14), N,N-diethyl-m-toluamide (DEET), ofloxacin and 3,3',4,4',5,5'-hexachlorobiphenyl (PCB-169) were detected in all samples. Most substances were found in sample taken from Çorlu Creek while, least substances were detected in sample taken from the source of Ergene River. The highest toxicity was reported in sample taken from near to Ergene-1 Organized Industrial Zone and at this sample 15 heavy metals and 33 micropollutants were detected. Especially, hexa(methoxymethyl)melamine, damascone, PCB-169, aluminum, nickel, boron and zinc were found in high concentrations. Although relation of each pollutant with toxicity showed that BAC-14, benzylamine, nonylphenol diethoxylate, PCB-169, BAC-12, dicyclohexylamine, celestolide were probably contributed to toxicity, the regression was relatively low. Moreover, relation between actual toxicity and predicted mixture toxicity derived by using Concentration Addition and Independent Action toxicity prediction models. When water quality and toxicity were examined, the highest pollution were observed in Çorlu and Ergene Creek which are under pressure of textile and leather organized industrial areas and domestic discharges. Outcomes of this study may contribute in understanding the risk of micropollutants in Ergene River and developing discharge limits for these pollutants.
Keywords: Micropollutants.